Questioni di diritto patrimoniale canonico. Alcune riflessioni a partire dagli adempimenti conseguenti alla riforma italiana in materia di Terzo settore (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. Lo stato dell’arte - 3. Enti ecclesiastici e Ets - 4. Enti ecclesiastici e libertà d’impresa - 5. Coerenza fra gli obblighi imposti dalla legge italiana e quelli previsti dal diritto canonico - 6. La scelta di adeguarsi alle norme italiane. I singoli adempimenti necessari. a) il regolamento - b) il patrimonio destinato - c) le scritture contabili.Canon property law issues. Some thoughts around the obligations arising from the new Italian Third Sector lawABSTRACT: The new Italian law in the field of the Third Sector provides for some burden on civilly recognized religious bodies, among which there are also Catholic ecclesiastical bodies. This paper deals with the canonical consequences of these obligations related to the general principles of Church law, as they are stated in the Code of Canon Law and the particular Italian canon law. The fulfillment of these government obligations is obviously not mandatory, however in many cases it may be timely, especially for institutions that already enjoy tax benefits that they could lose if they did not comply with the deadlines established by this new Italian law. Nevertheless, the central question is to verify whether certain obligations are lawful according to the Canon law. The essay raises the question of the provision of an “earmarked stock” and “internal rules” additional to their canonical Statutes, and especially the canonic assessment of commercial activities. If it is true that one has the right to do anything, but not everything is beneficial or constructive, catholic religious bodies should mind some questions before deciding to follow this law.
Keywords: Enti religiosi e Terzo Settore